Exploration and Identification of Entomopathogenic Fungi Isolated Spodoptera frugiperda from Sumbang, Banyumas Regency - Nur Kholida Wulansari; Ratna Dwi Hirma Windriyanti; Larin Tika Febrianti; Gita Anggraeni; Lafi Na’imatul Bayyinah; Endang Warih Minarni (Nusantara Science and Technology Proceedings, 2022)
Biological control of plant pests is an eco friendly controlling way with consideringeco-friendly of agroecosystem. Biological control does by usithe ng natural enemies introduced from the area and other areas. Biological control of plant pests can used by predators, parasitoids, and entombe opathogens. Identification of entomopathogenic fungi did at the integrated laboratory, Nahdlatul Ulama University, Purwokerto. The research method used is purposive sampling. Entomopathogenic fungi were identified and observed for macroscopic and microscopic characteristics. This study aims to determine the entomopathogenic fungi found in the corn cultivation center, Sumbang District, Banyumas Regency. The results of the study found there was Aspergillus spp in the corn cultivation center, Sumbang District, Banyumas Regency. Aspergillus spp was found to infect Spodoptera frugiperda. Aspergillus spp is reported can infect various types of insects so that it is effective in pest control.